Perceptions of the impact of individual allergic rhinitis symptoms: A survey of ARIA clinical experts - Sara Gil-Mata, MD; Tatiana Teixeira, MD; Anna Bedbrook, BSc; Jean Bousquet, PhD; Bernardo Sousa-Pinto, PhD; Rafael José Vieira, MD; Julijana Asllani; Habib Douagui; Estrella Asayag; Castro Maria Elizabeth; Carlos D. Crisci; René Maximiliano Gomez; et al. (World Allergy Organization Journal)
Background: Allergic rhinitis (AR) is a highly prevalent disease. We aimed to assess the symptoms that physicians who see patients with AR perceive as the most bothersome in their patients. Methods: We performed a cross-sectional study based on an online questionnaire sent to all members of the Allergic Rhinitis and its Impact on Asthma (ARIA) initiative. The survey included questions on the physicians' perceptions of patients’ AR symptoms as well as of their own AR symptoms. Results: Among 401 respondents, 155 (38.7%) reported having AR. ARIA members reported nasal symptoms to be the most frequent (89.7%) and bothersome (80.0%) symptoms experienced by themselves. Likewise, nasal symptoms were reported by ARIA members as the most frequent (94.8% in members with AR vs 96.0% in members without AR) and bothersome (57.0% in members with AR vs 67.9% in members without AR) in their patients. We found a significant association (p = 0.001) between physicians’ own symptoms and those perceived as the most bothersome in their patients. Conclusion: Physicians perceive nasal symptoms to be the most frequent and the most bothersome symptoms in AR patients. The physicians' personal experiences with AR may influence their perception of patients’ symptoms.